2002
DOI: 10.1139/t01-083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fines content on liquefaction strength and dynamic settlement of reclaimed soil

Abstract: In this study, the reclaimed soils in the Yunlin area of west Taiwan are adopted as test samples. The specimens were prepared by moist tamping at different relative densities and fines contents. Triaxial liquefaction tests were performed to evaluate the liquefaction strength and liquefaction-induced settlement. The test results show that the liquefaction strength of reclaimed soil increases as the relative density increases. In addition, under constant relative density, the liquefaction strength decreases as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 6 publications
2
15
1
2
Order By: Relevance
“…The interpreted trend of the CPT criteria does not provide consistent effects of non-plastic fines on liquefaction resistance with available laboratory-based correlations obtained by several previous researchers (e.g. Zlatovic and Ishihara, 1997;Polito and Martin, 2001;Chien et al, 2002;Thevanayagam and Martin, 2002;Kokusho, 2007;Cubrinovski et al, 2010).…”
Section: Introductioncontrasting
confidence: 70%
See 1 more Smart Citation
“…The interpreted trend of the CPT criteria does not provide consistent effects of non-plastic fines on liquefaction resistance with available laboratory-based correlations obtained by several previous researchers (e.g. Zlatovic and Ishihara, 1997;Polito and Martin, 2001;Chien et al, 2002;Thevanayagam and Martin, 2002;Kokusho, 2007;Cubrinovski et al, 2010).…”
Section: Introductioncontrasting
confidence: 70%
“…Zlatovic and Ishihara, 1997;Polito and Martin, 2001;Chien et al, 2002;Thevanayagam and Martin, 2002;Kokusho, 2007;Cubrinovski et al, 2010). The process in these studies was to directly compare the behavior of sand mixed with a specific amount of fines (less than 30% FC by weight) to that of the clean sand.…”
Section: Effects Of Fines and Relative Density On Liquefaction Resistmentioning
confidence: 99%
“…Reclaimed platforms can, however, be seriously affected by settlements, which may cause severe damage to buildings, highways, Over the past few years, the coastal area of Lingang New City, which extends for about 300 km 2 (45% of which was reclaimed from intertidal wetlands), has been subjected to broad modifications in its geomorphology and urban environment. Due to land reclamation, two main inherent problems have arisen: (i) liquefaction; and (ii) ground settlements, both of which are responsible for serious failures and damage to infrastructures of reclaimed foundations [12][13][14]. Results of geotechnical analyses have revealed that such a settlement usually continues over the entire reclamation facility lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Due to land reclamation, two main inherent problems have arisen: (i) liquefaction; and (ii) ground settlements, both of which are responsible for serious failures and damage to infrastructures of reclaimed foundations [12][13][14]. Results of geotechnical analyses have revealed that such a settlement usually continues over the entire reclamation facility lifetime.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, two main inherent problems arise for land-reclaimed areas: liquefaction and ground settlement and both of them may cause serious ground failures and damages to infrastructures on reclaimed foundations [12][13][14]. Moreover, the results of geotechnical analyses have revealed that such a kind of settlement continues over the entire reclamation facility lifetime.…”
Section: Introductionmentioning
confidence: 99%